Tingkat Kepatuhan Transfusi Darah pada Pasien Anak dengan Diagnosis Thalassemia di Rumah Sakit Umum Cut Meutia Aceh Utara - Arsyiva Putri Azhari; Mardiati Mardiati; Anna Millizia (Inovasi Kesehatan Global, 2025)
Thalassemia is an inherited blood disorder characterized by a deficiency of globin chain products in hemoglobin which results in low Hb levels. Blood transfusion is a treatment used in thalassemia patients. The purpose of this study was to determine the level of blood transfusion compliance in pediatric thalassemia patients at Cut Meutia General Hospital, North Aceh. The research method used a descriptive observational design, with 95 respondents and data collection using medical records and questionnaires. The results showed that 43.2% of respondents were predominantly early adolescents, 54.7% of respondents were predominantly male, 42.1% of respondents were predominantly blood type O, 58.9% of respondents had hemoglobin levels ≥7 g/dl, 87.4% of respondents had a blood transfusion frequency of 2-4 weeks. 53.7% of respondents had high compliance. Based on this, it can be concluded that the level of blood transfusion compliance in pediatric thalassemia patients at Cut Meutia General Hospital, North Aceh, mostly had high compliance.